To factor an expression using GCF we need to first factorate the numbers. We have:
![\begin{gathered} 24=2\cdot2\cdot2\cdot3 \\ 36=2\cdot2\cdot3\cdot3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/zzf4dmo03r1re68xa5edqu6jmhdj6d84or.png)
We now need to take the factors that repeat. We have "2" repeating twice and "3" repeating once. So we have:
![GCF=2\cdot2\cdot3=12](https://img.qammunity.org/2023/formulas/mathematics/college/utfwm8smk8rk6v5t8r4e45s4jrlhff76mw.png)
GCF= 2*2*3=12
We now divide both numbers by the GCF, we have:
![(24)/(12)=2](https://img.qammunity.org/2023/formulas/mathematics/college/4f6325u4r992z0ldi0e2uy50xx1852e6v4.png)
![(36)/(12)=3](https://img.qammunity.org/2023/formulas/mathematics/college/hkp6uqmmyeaohs3k0k3rnyp8hjzw4jsghy.png)
We can represent the expression as the product of the GCF with the divisions above.
![12\cdot(2+3)](https://img.qammunity.org/2023/formulas/mathematics/college/v1wl4kg8xnutxcx7bhi04rwrbqtne1ppv3.png)